Anchoring capital in place: The grounded impact of international wealth chains on housing markets in London. (January 2020) - McKenzie, Rex; Atkinson, Rowland
Taking as our focus the city of London over the last decade, we use state-held records of house sales to consider the impact of competition for housing resources in the luxury property market. This data suggests that the use of offshore investment vehicles and the concealment of wealth from national tax agencies have become key mechanisms by which housing resources have been exploited by the wealthy and their capital deployed by agents of the rich. Using the concept of wealth chains, we consider these methods of capital accumulation as these extending flows of managed capital become 'anchored' within specific urban spaces, in this case the luxury housing market of inner West London. Our analysis of a selection of these chains shows that the prevailing political management of the property economy benefits those already winning the war of inequality while looking to augment their capital and shield it from tax and regulation. The ultra-wealthy, financial intermediaries and multinational corporations have created chains articulated across space, with the effect of undermining the value of dwellings as homes, and have replaced them with assets to be traded in pursuit of private and offshore wealth gains. The result is an urban context that favours already advantaged and powerful interests and enables the avoidance of tax obligations desperately needed at a time of austerity and intense housing need.